The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1960
DOI: 10.1086/626637
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Frequency of Forces in Geomorphic Processes

Abstract: Abstract:At the Satino site in the center of the Russian Plain, major events of the Holocene erosion history are concentrated on sides of river valleys incised into smooth moraine landscape. Valley sides are dissected by Pleistocene gullies. Extraordinary for the Holocene was formation of four new permanent gullies. Three of them had appeared in the Late Atlantic -Early Subboreal time. One gully permitted direct dating of the fan base, which gave estimation of its appearance between 4.3-4.6 ka BP (cal). Two ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

62
1,307
3
38

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,682 publications
(1,410 citation statements)
references
References 16 publications
62
1,307
3
38
Order By: Relevance
“…In terms of their geometry, alluvial rivers are self-forming and operate most effectively by moving water and sediment from their drainage basins under conditions approximating bankfull flow (Wolman and Miller, 1960). They exhibit stable channel geometries, which can be predicted with reasonable accuracy using 'regime theory' for stable canals (Lacey, 1929(Lacey, , 1933(Lacey, , 1946(Lacey, , 1958Blench, 1952Blench, , 1969Blench, , 1970Simons and Albertson, 1960) and 'hydraulic geometry' for stable river channels (Leopold and Maddock, 1953;Parker, 1979;Huang and Warner, 1995;Huang and Nanson, 1995, 1998.…”
Section: Clarifying the Confusion Of Multiple Extremal Hypothesesmentioning
confidence: 99%
“…In terms of their geometry, alluvial rivers are self-forming and operate most effectively by moving water and sediment from their drainage basins under conditions approximating bankfull flow (Wolman and Miller, 1960). They exhibit stable channel geometries, which can be predicted with reasonable accuracy using 'regime theory' for stable canals (Lacey, 1929(Lacey, , 1933(Lacey, , 1946(Lacey, , 1958Blench, 1952Blench, , 1969Blench, , 1970Simons and Albertson, 1960) and 'hydraulic geometry' for stable river channels (Leopold and Maddock, 1953;Parker, 1979;Huang and Warner, 1995;Huang and Nanson, 1995, 1998.…”
Section: Clarifying the Confusion Of Multiple Extremal Hypothesesmentioning
confidence: 99%
“…The question of whether, over the longer term, the total mass of sediment moved during periods of high flow (with their low frequency of occurrence) exceeds that transported by more frequently occurring, lower-flow conditions is a long-standing one in fluvial geomorphology [Wolman and Miller, 1960;Pickup and Warner, 1976;Nash, 1994]. Indeed, Pickup and Warner [1976] found that for bed load transport within a relatively small creek near Sydney, flows of moderate magnitude and frequency dominated net bed load transport.…”
Section: Importance Of High-flow Periods In Long-term Suspended Sedimmentioning
confidence: 99%
“…The importance of the frequency spectra of g½omorphic events is a fundamental problem in g½omorphic research. Much of the previous research on this problem has focused on defining the recurrence interval of the most effective g½omo•hic event, with "effectiveness" defined either on the basis of denudation rate [e.g., Wolman and Miller, 1960 Wolman and Gerson, 1978]. Scant attention has been paid, however, to the question of how intrinsic variability in g½omo•hic forces impacts the morpholo• and ra•½ of evolution of landforms.…”
Section: Introductionmentioning
confidence: 99%